2017
DOI: 10.3386/w24147
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Concentration

Abstract: Ransom for helpful comments. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w24147.ack NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(32 citation statements)
references
References 1 publication
3
27
1
1
Order By: Relevance
“…I focus here on market power in output markets. Of course, firms can also exercise market power in the markets for their inputs, including labor; for discussions, seeManning (2003),Azar, Marinescu, and Steinbaum (2017), Benmelech, Bergman, andKim (2018), andKrueger (2018).…”
mentioning
confidence: 99%
“…I focus here on market power in output markets. Of course, firms can also exercise market power in the markets for their inputs, including labor; for discussions, seeManning (2003),Azar, Marinescu, and Steinbaum (2017), Benmelech, Bergman, andKim (2018), andKrueger (2018).…”
mentioning
confidence: 99%
“…In this paper, we contribute to this growing debate by calculating measures of market concentration in local labor markets for the near-universe of 2016 online vacancy postings constructed by Burning Glass, and building on Azar, Marinescu and Steinbaum (2017). We have shown that concentration is high (above 2,500 HHI) in 54% of US labor markets according to our baseline market definition, and in at least a third of US labor markets according to alternative labor market definitions.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we directly quantify the level of labor market concentration across nearly all occupations and for every commuting zone in the US, building on our findings in Azar, Marinescu and Steinbaum (2017). The earlier paper used data for the most frequent occupations from a large online job board (CareerBuilder.com) to show that higher concentration is associated with lower posted wages.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it has been suggested that policy-makers develop a broader list of criteria to take into account in defining the existence of labour market power. These recommendations include the following:  a (rebuttable) presumption that 'a market share of over 50% of employment (or alternatively, of posted job vacancies) in a well-defined antitrust (labour) market' may constitute evidence of market power';  '(t)he ability to lower wages below what would be charged in a competitive market';  '(t)hee ability to wage-discriminate, that is, to pay similar workers working in the same market significantly different wages';  '(t)he ability to impose disadvantageous nonwage contractual terms on workers without compensation' 165 . One may also argue for the analysis of the superior bargaining power of some employers, in view for instance of significant investments made by the workers for their education and training for the specific job, which make it quite difficult for them to switch if these costs are non-recoverable in their new job or occupation.…”
Section: Designing Competition Law For Labour Market Power Regulationmentioning
confidence: 99%